Identifikasi Miskonsepsi Peserta Didik Pada Materi Sistem Pencernaan Manusia Di Sekolah Dasar - Agustina, Tintin; Hamdu, Ghullam; Putri, Agnestasia Ramadhani (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is motivated by the existence of problems in the form of low conceptual understanding possessed by students in the material of the human digestive system. One of the causes of students' low understanding of concepts in the human digestive system material is due to misconceptions or misunderstandings of concepts. As for research on the identification of Student Misconceptions in the Material of the Human Digestive System in Elementary Schools, the aim is to describe misconceptions, along with knowing the causes of misconceptions. While the research method used in this study with a descriptive qualitative approach. The data collection instruments were in the form of essay test questions, interviews and documentation. The results showed that the average misconception experienced by students in the human digestive system material was 55.65% greater than the understanding category of 33.47% and the non-understanding category of 10.86%. Factors that cause students' misconceptions about the material of the human digestive system are caused by preconceptions, incomplete reasoning, wrong intuition, learning methods or methods used, associative thinking and abilities possessed by students, the teacher/teaching factor lacks mastery of learning materials, lack of interest of students in learning and language context. This research is expected to be a reference regarding identifying misconceptions experienced by students in the subject of the human digestive system.